On Regularized Trace of a Differential Operator of Second Order - Gul, Erdal; Ucuncu, Duygu (AMER INST PHYSICS, 2016)
In this work, a formula for the regularized trace of second order differential operator given in a finite interval which has unbounded operator coefficients is found.
Keywords: Physics